Collagenous colitis: a distinctive and potentially reversible disorder. Issue 3 (March 1982) - Pieterse, A S; Hecker, R; Rowland, R
Abstract : A case of collagenous colitis is reported. The patient's symptoms cleared up after a course of mepacrine hydrochloride. Biopsies taken after clinical recovery still showed some increase in the number of reticulin fibres present in the upper layers of the lamina propria but the subsequent six years.